Potential Roles of n-3 PUFAs during Skeletal Muscle Growth and Regeneration - Tachtsis, Bill (Nutrients, 2018)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs), which are commonly found in fish oil supplements, are known to possess anti-inflammatory properties and more recently alter skeletal muscle function. In this review, we discuss novel findings related to how n-3 PUFAs modulate molecular signaling responsible for growth and hypertrophy as well as the activity of muscle stem cells. Muscle stem cells commonly known as satellite cells, are primarily responsible for driving the skeletal muscle repair process to potentially damaging stimuli, such as mechanical stress elicited by exercise contraction. To date, there is a paucity of human investigations related to the effects of n-3 PUFAs on satellite cell content and activity. Based on current in vitro investigations, this review focuses on novel mechanisms linking n-3 PUFA’s to satellite cell activity and how they may improve muscle repair. Understanding the role of n-3 PUFAs during muscle growth and regeneration in association with exercise could lead to the development of novel supplementation strategies that increase muscle mass and strength, therefore possibly reducing the burden of muscle wasting with age.